Contraintes et enjeux de développement de la Nouvelle-Calédonie - Christian Jost (EchoGéo)
In 2008 a vast consultation was launched in New Caledonia aimed at establishing a development plan for the territory, directed at the year 2025. If the Caledonian economy has experienced high growth over the past decade, thereby satisfying population and investment needs, the current challenge resides in the capacity to build the society of the future based on the recognition of multi-cultural aspirations and a shared project. Envisaged by the Accord de Nouméa and launched ten years later, the SAD offers all New Caledonians the opportunity to plan the future together. The over-arching strategic reflection and the creation of the broad politic foundations for the project have yet, however, to be determined.